Synergism between genome sequencing, tandem mass spectrometry and bio-inspired synthesis reveals insights into nocardioazine B biogenesis1. Issue 26 (14th July 2015) - Alqahtani, Norah; Porwal, Suheel K.; James, Elle D.; Bis, Dana M.; Karty, Jonathan A.; Lane, Amy L.; Viswanathan, Rajesh
<x xml:space="preserve">Abstract</x> A noz gene cluster encoded by Nocardiopsis sp. CMB M0232 is presented, revealing the actinomycetes' unique indole methylating and prenylating patterns, leading to anticancer nocardioazine alkaloids.